1992
DOI: 10.1002/smr.4360040303
|View full text |Cite
|
Sign up to set email alerts
|

Document quality indicators: A framework for assessing documentation adequacy

Abstract: This paper presents the results of an ongoing investigation that focuses on assessing the adequacy of project documentation through an identified taxonomic structure relating numerous documentation characteristics. Previous research in this area has been limited to the study of isolated characteristics of documentation and English prose, without considering the collective contributions of such characteristics. The research described in this paper takes those characteristics, adds others, and establishes a well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Although there is no framework to assess the quality of technical cookbooks, at the best of our knowledge, there has been some work on assessing technical documents. Arthur and Stevens [27] developed a taxonomy for evaluating documentation, where an adequate documentation has four qualities: accuracy, completeness, usability, and expandability. Smart [28] studied quality factors for technical documentation in the context of software quality documents [28], and proposed three dimensions to evaluate documentation quality: easy to use (i.e.…”
Section: Cookbook Assessmentmentioning
confidence: 99%
“…Although there is no framework to assess the quality of technical cookbooks, at the best of our knowledge, there has been some work on assessing technical documents. Arthur and Stevens [27] developed a taxonomy for evaluating documentation, where an adequate documentation has four qualities: accuracy, completeness, usability, and expandability. Smart [28] studied quality factors for technical documentation in the context of software quality documents [28], and proposed three dimensions to evaluate documentation quality: easy to use (i.e.…”
Section: Cookbook Assessmentmentioning
confidence: 99%
“…These requirements do not only guide the design of the template but also its evaluation. Dautovic et al, (2011), Hargis et al, (2014), Arthur & Stevens (1990), and ISO/IEC 26514 (2008) have identified a number of generic requirements on documentation templates. These have been used as a basis for the specific requirements for the BP Document Template.…”
Section: The Low Quality Of Bp Documentation Can Impede the Use Of Bpmentioning
confidence: 99%
“…Another framework for assessing documentation adequacy is also presented in [20], the authors mainly used a predefined taxonomic structure to assess a project documentation which funded by Naval Surface Warfare Systems (NSWC). Based on their findings of the authors, there is a need for a tool and method that can automatically evaluate any software documentation quality especially for large systems.…”
Section: Related Workmentioning
confidence: 99%